2022
DOI: 10.1007/s10238-021-00787-9
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of admission levels of P, E and L selectins as predictors for thrombosis in hospitalized COVID-19 patients

Abstract: Thromboembolic complications are the most reported cause of death in coronavirus disease-2019 (COVID-19). Hypercoagulability, platelets activation and endotheliopathy are well-recognized features in COVID-19 patients. The aim of this work was to evaluate circulating soluble selectins P, E and L at the time of hospital admission as predictors for upcoming thrombosis. This retrospective study included 103 hospitalized COVID-19 patients and 50 healthy volunteer controls. COVID-19 patients were categorized into tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 30 publications
4
36
0
Order By: Relevance
“…We did not observe increased P-selectin plasma levels, but they were reduced in female vs. male COVID-19 and post-COVID-19 patients. Higher levels of soluble P-selectin and E-selectin were detected in COVID-19 patients as predictors of thrombosis, while E-selectin levels are predictive of ICU admission [49,50]. We observed increased E-selectin plasma levels in female COVID-19 and post-COVID-19 patients.…”
Section: Discussionmentioning
confidence: 51%
“…We did not observe increased P-selectin plasma levels, but they were reduced in female vs. male COVID-19 and post-COVID-19 patients. Higher levels of soluble P-selectin and E-selectin were detected in COVID-19 patients as predictors of thrombosis, while E-selectin levels are predictive of ICU admission [49,50]. We observed increased E-selectin plasma levels in female COVID-19 and post-COVID-19 patients.…”
Section: Discussionmentioning
confidence: 51%
“…Previous studies have confirmed the role of L-selectin in the inflammatory process, particularly in the recruitment of inflammatory cells [ 26 , 27 , 28 , 29 , 30 , 31 ]. Population studies have observed an association between adhesion molecule concentrations and age.…”
Section: Discussionmentioning
confidence: 71%
“…In this article, we considered cellular markers according to current immunological literature and dictations from experts in the field. Many senior scientists between April and September 2020 wrote letters in this regard (see Supplementary Materials ) that demonstrated overall infection antibody positivity of 23% (NY), 18% (London), and 11% (Madrid) are dependent on the other 10 or more T cell subtypes performing all the regulatory functions of the immune system, which are arguably more important in all pathologies [ 427 , 428 , 429 , 430 , 431 , 432 , 433 , 434 , 435 , 436 , 437 , 438 , 439 , 440 , 441 , 442 , 443 , 444 , 445 ]. To conclude this review, we hope that the biomolecular information provided is prioritized in clinical and therapeutic trials, and expanded upon to better ensure patient care, therapeutic development, transmission, and mortality rates are improved world-wide, to more accurately target COVID-19 and similar pathologies that also host dystopian properties, and the details within will provide further information for all future researchers.…”
Section: Discussionmentioning
confidence: 99%